Analisis Kalām Khabari dalam Kitab Lubāb al-Hadīṡ Karya Jalaluddin al-Suyuthi - Ahmad Fajar; Taufik Luthfi (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2022)
This study focuses on one of the works of Jalaluddin bin Kamaluddin al-Suyuthi, namely Lubāb al-Hadith which consists of forty chapters, each chapter contains ten Hadīṡ with a total of four hundred Hadīṡ. This book contains about the virtues, prohibitions and prevention of the Hadīṡ of the Prophet, the hadith Qudsi and Aṡar. The purpose of this study was to find out Kalām Khabari and its various types contained in the book of Lubāb al-Hadith. The research method used in this research is the literature study method, which is a series of activities related to the methods of collecting library data, reading and taking notes, then processing research materials. Of the four hundred Hadīṡ in forty chapters, Forty Hadīṡ have been taken as samples in this study. So the results of the analysis of the Lubāb al-Hadīṡ book found that 88% of Kalām Khabar Ibtidā’I and 12% of Kalām Khabar Ṭalabi were found, while Kalām Khabar Inkāri was not found.